2022
DOI: 10.1108/ejim-01-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Front-end of innovation: a systematic review and lifecycle analysis

Abstract: PurposeThis study investigates the intellectual structure of the front-end of innovation (FEI) research field and elaborates a lifecycle model, which embraces the FEI progress and conceptual development.Design/methodology/approachThis study analysed 355 papers published from 1987 to 2020 in the Scopus and Web of Science databases through bibliometrics, network analysis and content analysis.FindingsThis study reveals FEI research themes and topics and explores their evolution through three periods. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…The theoretical background presented on FFE allowed a historical overview of this construct, the identification of how the key issues in FFE have evolved and also of the existing gaps in FFE. As indicated by various authors (Joachim & Spieth, 2020;Oliveira et al, 2022;Park et al, 2021), research on FFE has advanced but it is still not a consolidated topic in the literature. On the other hand, the theoretical referential on the degree of product innovation and its relationship with flexibility and iteration and the creative process, provide tools to analyze and understand the FFE from two dimensions: degree of innovation and time (project stage).…”
Section: Analysis Of Ffe Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical background presented on FFE allowed a historical overview of this construct, the identification of how the key issues in FFE have evolved and also of the existing gaps in FFE. As indicated by various authors (Joachim & Spieth, 2020;Oliveira et al, 2022;Park et al, 2021), research on FFE has advanced but it is still not a consolidated topic in the literature. On the other hand, the theoretical referential on the degree of product innovation and its relationship with flexibility and iteration and the creative process, provide tools to analyze and understand the FFE from two dimensions: degree of innovation and time (project stage).…”
Section: Analysis Of Ffe Modelsmentioning
confidence: 99%
“…FFE became a topic of study over the last three decades with an increasing relevance, as demonstrated by the growing number of publications on the subject in the last 15 years (Borgianni et al, 2018;Costa & Toledo, D 2016;Joachim & Spieth, 2020;Oliveira et al, 2022;Park et al, 2021;Takey & Carvalho, 2016); thus, research on FFE shows significant advances. From the late 1980s to the early 2000s, FFE research focus was on process, under the context of incremental innovation (Cooper, 1988;Khurana & Rosenthal, 1997;Reinertsen & Smith, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2. Research works on front end of innovation (FEI) analysis models (adapted from [47,[50][51][52]).…”
Section: Front End Of Innovation (Fei)mentioning
confidence: 99%
“…The front-end stages of innovation play a crucial role as product concepts developed during this phase serve as a foundation for decision-making in subsequent development stages (de Oliveira et al ., 2022). Generating innovative product concepts requires diverse teams to work together and integrate their knowledge, ideas and perspectives (Aggarwal and Woolley, 2019).…”
Section: Introductionmentioning
confidence: 99%